Factors Contributing to Adoption of Improved Agricultural Technologies. - Puri, Peshal K. (Tufts University. Tisch Library., 2020)
This poster identifies factors associated with increased adoption of improved agriculture technology and management practices.; Feed the Future Innovation Lab for Nutrition, USAID Contract No. AID-OAA-L-10-000006, managed by Tufts University's Gerald J. & Dorothy R. Friedman School of Nutrition Science and Policy